Facile Synthesis of Graphene Oxide-Nano Titania Composites and Evaluation for Visible Light Assisted Photocatalytic Degradation of Rhodamine B - Ryali, Soma Sekhar; Sanasi, Paul Douglas (Asian Journal of Chemistry, 2018)
Nano titania composite materials exfoliated with varying weight percentage of graphene oxide were synthesized and evaluated for visible light assisted photocatalytic degradation of rhodamine-B. Titanium tetrachloride was hydrolyzed in water medium under organic solvent free conditions followed by ultrasonic addition of the as prepared 1 % aqueous solution of graphene oxide. The morphology and structural properties of the composite materials (1, 2, 5, 10, 15 wt % graphene oxide-nano titania) prepared has been characterized using X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), UV-visible diffuse reflectance spectra (UV-Vis DRS), high resolution transmission electron microscope (HRTEM), field emission-scanning electron microscopy (FESEM) and UV-visible spectroscopy. A superior activity was observed with 10 mg of 10 % graphene oxide-nano titania composite material. The 100 % degradation of rhodamine-B was observed in 60 min and other optimum conditions were established.